Pengaruh Kompetensi, Komitmen, Kepuasan Terhadap Loyalitas Yang Berdampak Kepada Kinerja Account Officer Kredit Umkm Bank Bjb - Eko Singgih Priyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to analize: (1) The effect of competence, commitment, satisfaction account officer credit of SMEs on loyalty of account officer credit of SMEs, (2) The effect of competence, commitment, satisfaction and loyalty of account officer credit of SMEs on the performance of account officer credit of SMEs at PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk. The type of research used is descriptive which is a study that aims to determine the casual relationship of a phenomenon or problem solving studied to see how far the influence of independent variables on the dependent variables. Population research this is the whole account officer credit of SMEs PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk. Which recorded a total of 244 account officer credit of SMEs taken using the simple random sampling. Collecting data in study is in the form of a questionnaire consist of the questions that have five alternative answers using a Linkert Scale. The statistic methode used in this study is Structural Equation Modeling (SEM) which operate through the LISREL program.